The Use of Instagram to Enhance Students’ Creative Writing Skills: A Systematic Literature Review - Nugraheni, Sinthya Irawati; Priyatmojo, Arif Suryo (Universitas Pahlawan Tuanku Tambusai, 2025)
Creative writing is essential in fostering students' ability to express ideas and emotions, yet it remains underemphasized in EFL classrooms due to perceived challenges and low motivation among learners. The rise of digital platforms, particularly Instagram, presents an opportunity to enhance creative writing by leveraging its multimodal and interactive features. Despite growing interest in social media’s educational potential, a comprehensive synthesis of Instagram’s role in creative writing instruction remains underexplored. This conceptual review examines how Instagram can support EFL students’ creative writing by analyzing 30 scholarly articles through a systematic literature review and VOS viewer-based keyword mapping. Findings indicate that Instagram’s visual and interactive affordances—such as captions, stories, and hashtags—effectively stimulate creativity, improve narrative construction, and foster engagement through peer feedback and authentic audiences. The platform also promotes digital literacy and learner autonomy by bridging formal and informal learning environments. However, challenges like digital distractions and privacy concerns necessitate structured pedagogical integration. The study concludes that Instagram, when used strategically, can enhance creative writing skills by aligning with students’ digital practices, though further research is needed to assess long-term impacts across diverse learner contexts. These insights offer practical recommendations for educators to design scaffolded, multimodal writing tasks that leverage Instagram’s features while addressing ethical considerations. The implications highlight the transformative potential of social media in making creative writing more accessible, engaging, and relevant for 21st-century learners.